PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 014 BANGKO MAKMUR - Nur Fatimah; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was aimed to increase students’ achevement of matematics in V grade year of 2014/2015. The subject of this research is students V grade of State Elementary School 014 Bangko Makmur which is total of 25 students, consited of 12 girls and 13 boys. This was a classroom research which has two cycles which was conducted on April 02nd to May 23th 2015. The data shown that either students’ achievement increased. This was found from students’ and teacher’s scores in students’ achievement increased. First cycle at the first meeting teacher’s activity was 66.67% categorized as enough and increased 8.33% at the second meeting 75% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 83.33% categorized as very good and the second meeting it increased as 8.34% so the percentage became 91.67%. At the first cycle in the first meeting, the percentage of students’ activities was 58.33% categorized as enough and the second meeting it increased as 8.34% so became 66.67% categorized as good. At the second cycle in the first meeting it increased to 83.33% categorized as good. At the second meeting the percentage of students’ activities increased as 4.17% became 87.5% categorized as good. However, students’ achievement also increased. The basic score of daily examination as 11.6% which 19 students passed and 8 students failed. Based on the explanation above it can be concluded that the implementation learning through Cooperative Learning Student Teams Achievement Division increased students’ achievement the result of Mathematic studies at five grade of State Elemantary School 014 Bangko Makmur.Key Words : Cooperative Learning Thype Student Teams Achievement Division (STAD), Students’ Achevement the Result of Mathematic Studies